2020
DOI: 10.5937/scriptamed51-24916
|View full text |Cite
|
Sign up to set email alerts
|

Association of body mass index with progression and prediction of multiple sclerosis

Abstract: Background/Aim: Multiple sclerosis is a disease whose aetiology involves multifactorial interactions among genetic and environmental factors. Obesity is one of the most important environmental factors conducive to the onset and progression of the disease. The aim of the study was to determine the value of body mass index (BMI) in a population of patients with multiple sclerosis compared to the general population, in order to assess the relation between the BMI and physical disability in patients with multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“…Zamzam et al also showed that higher-BMI patients had higher EDSS scores (95% CI 0.17-0.21). These findings were contrary to those of Tadić et al, who found no evidence of a significant association between BMI and EDSS score [ 28 , 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Zamzam et al also showed that higher-BMI patients had higher EDSS scores (95% CI 0.17-0.21). These findings were contrary to those of Tadić et al, who found no evidence of a significant association between BMI and EDSS score [ 28 , 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…8,13 Our findings are also in line with observational studies that identified no link between NFM and disability progression in MS. 8 By contrast, our findings are in disagreement with the results of other observational studies that identified no evidence of an association between disability progression in MS and adiposity-related measures, with respect to BMI, FM or FP. 14,15 The lack of association in these studies is more likely due to the small sample size, which ranged from 27 to 150 participants, which reduces the power to detect the true effect.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas some studies report evidence supporting the association between higher BMI, fat mass (FM), fat percentage (FP) and disability progression in MS, 8,13 other studies have identified no evidence of an association between disability progression in MS and BMI, FM or FP. 14,15 The MR approach is an epidemiological technique that utilises genetic variants as proxies to investigate the causal role of a modifiable exposure on an outcome of interest. 16 Therefore, MR studies are less prone to bias from confounders, reverse causation and other biases that raise questions regarding the findings from observational studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation